Identification of Options and Policy Instruments for the Internalisation of External Costs of Electricity Generation. Dissemination of External Costs of Electricity Supply Making Electricity External Costs Known to Policy-Makers MAXIMA - Anil Markandya; Alberto Longo (Fondazione Eni Enrico Mattei (FEEM), 2005)
In the present paper, after reviewing the results of the ExternE project and its follow-up stages in the estimation of the external costs of electricity production, we look at the policy instruments for the internalisation of such costs. Emphasis is given to subsidies, such as feed-in tariffs, competitive bidding processes and tradable green certificates to stimulate the use of renewables in the production of electricity. When policy-makers are asked to choose the instrument(s) to internalise the externalities in the electricity production, they have to find a solution that gives the best outcome in terms of efficiency, cost minimisation, impact on the job market, security of energy supply, equity of the instrument, technological innovation, certainty of the level of the internalisation, and feasibility. The choice of the instrument will require some trade-offs among these criteria. Conjoint choice analysis can help in investigating how stakeholders and policy makers trade off the criteria when choosing a policy for the internalisation of the externalities. In this paper we present the first results of a questionnaire that employs conjoint choice questions to find out how policy makers and stakeholders of the electricity market trade off some socio-economic aspects in the selection of the policy instruments for the internalisation of the externalities. The results of this first set of interviews will be useful for further research.
Keywords: Q42; Q48; Q51; 330; Policy instruments; ExternE; External costs; Electricity; Conjoint choice analysis